The Potential Use of Cold-Pressed Coconut Oil By-Product as an Alternative Source in the Production of Plant-Based Drink and Plant-Based Low-Fat Ice Cream: The Rheological, Thermal, and Sensory Properties of Plant-Based Ice Cream - Muhammed Zahid Kasapoglu; Osman Sagdic; Esra Avci; Zeynep Hazal Tekin-Cakmak; Salih Karasu; Rabia Sena Turker (Foods, 2023)
This study aimed to investigate the potential use of cold-pressed coconut oil by-products (COB) as a low-cost alternative source for plant-based drink and ice cream production. Firstly, a plant-based drink was produced from cold-pressed coconut oil by-products (COB drink) and compared with a commercial coconut drink. The fat, protein, and zeta potential values of coconut drink obtained from COB were higher than those of the commercial samples. In addition, the particle size value of the drink obtained from COB was found to be lower than that of the commercial drink. In the second stage, full-fat and low-fat plant-based ice cream samples using COB drink were produced and compared to control ice cream samples (produced by the commercial coconut drink) in terms of rheological, sensorial, and thermal properties. Rheological analysis showed that all plant-based ice cream samples indicated pseudoplastic, solid-like, and recoverable characteristics. Low-fat commercial control ice cream samples (C1) indicated the lowest K value (9.05 Pasn), whereas the low-fat plant-based ice cream sample produced by the COB drink (COB-3) exhibited the highest K value (17.69 Pasn). ΔHf values of the plant-based ice cream samples varied from 144.70 J/g to 172.70 J/g. The low-fat COB ice cream stabilized with 3% COB and full-fat COB ice cream samples showed lower ΔHf values than control ice cream samples, indicating that the COB ice cream showed desired thermal properties. The COB drink may be utilized in plant-based ice cream without altering sensory qualities, and low-fat ice cream could be manufactured in the same manner to attain full-fat ice cream quality characteristics. The results of this study demonstrated that COB can be successfully used as an inexpensive raw material source in the production of full-fat and reduced-fat vegetable-based ice cream.